Effects of Air Polishing Powders on the Surface Roughness of Composite Resins - Gürler, Ali Tümay; Duran, I.; Yücel, A.C.; Özkan, P. (Association for Dental Sciences of the Republic of China, 2010)
Background/purpose: Although new composites are being introduced into clinical practice to achieve better polishability and wear resistance, their properties and the surface changes that occur after air polishing are still unknown. The aim of this study was to investigate the effects of different air polishing powders on the surface roughness of different types of composite resin restorative materials. Materials and methods: Thirty cylindrical specimens (15 × 2 mm) were prepared for each of seven composite resin restorative materials. All specimens were polished with a series of aluminum oxide polishing discs (Sof-Lex). Prepared specimens of each composite resin were randomly divided into three groups of 10 specimens each, including a control (Group C) and two different air-powder applications (Group CP, Cavitron Prophy-Jet; and Group PS, Sirona ProSmile prophylaxis powder). A standard air polishing unit (ProSmileHandly) was used. All specimens were air-polished for 10 seconds at a pressure of 4 bar. The distance of the spray nozzle from the specimens was approximately 10 mm, and the angle of the nozzle was 90°. Surface roughness measurements (Ra, μm) were performed using a profilometer (Perthometer M2). Data were analyzed by two-way analysis of variance (ANOVA), and mean values were compared by Tukey's honestly significant difference test (a = 0.05). Results: According to the two-way ANOVA, composite resins, air polishing powders, and their interactions were statistically significant (P < 0.05). For the CeramXMono, Grandio, Filtek Silorane, and Quixfil composite resin restorative material groups, the highest Ra values were observed in Group PS. No significant difference was observed between Group PS and Group CP (P > 0.05), and these groups demonstrated the highest Ra values for the Aelite Aesthetic Enamel, FiltekZ250, and IntenS composite resin restorative materials. The lowest Ra values for the composite resin groups were observed in Group C (P < 0.05). When comparing composite resins, FiltekZ250 demonstrated statistically significantly lower Ra values than the other composite resins tested (P < 0.05). No significant difference was observed between the IntenS and Quixfil composite resin groups; these groups also demonstrated the highest Ra values. Conclusion: Air polishing applications increased the surface roughness of all composite resin restorative materials tested. Composite restorations may require re-polishing after air polishing. © 2010 Association for Dental Sciences of the Republic of China.
Keywords: Air Polishing; Composite Resin; Silorane; Sodium Bicarbonate; Surface Roughness